Geographically Localized Medicine House-Staff Teams and Patient Satisfaction. (March 2019) - Siddiqui, Zishan; Bertram, Amanda; Berry, Stephen; Niessen, Timothy; Allen, Lisa; Durkin, Nowella; Feldman, Leonard; Herzke, Carrie; Qayyum, Rehan; Pronovost, Peter; Brotman, Daniel J
Background: Geographically localized care teams may demonstrate improved communication between team members and patients, potentially enhancing coordination of care. However, the impact of geographically localized team on patient experience scores is not well understood. Objective: To compare experience scores of patients on resident teams home clinical units with patients assigned to them off of their home units over a 10-year period. Participants: Patients admitted to any of the 4 chief resident staffed internal medicine inpatient service were included. Patients admitted to the house-staff teams' home clinical unit comprised the exposure group and their patients off of their home units comprised the control patients. Measurement: Top-box experience scores calculated from the physician Hospital Consumer Assessment of Healthcare and Provider Systems (HCAHPS) and Press Ganey patient satisfaction surveys. Results: There were 3012 patients included in the study. There were no significant differences in experience scores with physician communication, nursing communication, pain, or discharge planning between the 2 groups. Patients did not report satisfaction more often with the time physicians spent with them on localized teams (48.6% vs 47.5%; P = .54) or that staff were better at working together (63.2% vs 61.3%; P = .29). This did not change during a 45-month period when the proportion of patients on home units exceeded 75% and multidisciplinary rounds were started. Conclusion: Patients cared for by geographically localized teams did not have better patient experience. Other factors such as physician communication skills or limited time spent in direct care may overshadow the impact of having localized teams. Further research is needed to better understand organizational, team, and individual factors impacting patient experience.